The status of care for youth with type 1 diabetes within and coming from humanitarian crises settings: a narrative review - Steven James; Samira B. Jabakhanji; Roopa Mehta; John McCaffrey; Maisoon Mairghani; Dominika Bhatia; Olive James; Sylvia Kehlenbrink; Philippa Boulle; Kiran Mejia Mehta; David Simmons; Edward W. Gregg (Conflict and Health)
Abstract Background Humanitarian crises bring unique, and potentially growing challenges to people with type 1 diabetes (T1D). We aimed to determine, in youth with T1D (mean age (± 1SD) 0–17.9 years) within and coming from humanitarian crises settings (HCS), the reported prevalence that meet international consensus targets for glycaemic, blood pressure and lipid management, and incidence of severe hypoglycaemia or diabetic ketoacidosis. Methods A narrative review of quantitative data was conducted, using a systematic process. MEDLINE (Ovid), Global Health, Web of Science, Scopus, Embase, CINAHL, APA PsycINFO, Cochrane trials, and the reference lists of eligible records were searched (January 2014-February 2024); ten records covering ten separate studies were retrieved. Results Glycaemic management was consistently suboptimal in HCS. However, among individuals coming from HCS, glycaemia varied. Across both groups, data relating to blood pressure, lipids, severe hypoglycaemia or diabetic ketoacidosis were either unavailable or limited. Conclusion Findings expose the dearth of data relating to defined youth with T1D within and coming from HCS, leaving the status of this population largely uncharacterised. With limited data indicating suboptimal T1D management, there is a pressing need for the development of a consensus guideline on, and core indicators relating to such youth within and coming from HCS, plus monitoring systems and outcome data.